The concept of human security: characteristics, dimensions and determinants - Alkeyeva Д.С.; Bulegenova Б.Б.; Alkeyev А.К.; Avcu С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
This article is called to present some theoretical foundations of the concept ‘security’ both in its traditional sense as that of a state and its territorial integrity, and in its newer sense according to which the human is the entity to be cared for first and foremost, with the accent made on the latter. It examines the underlying premises and evolution of such a human-centered approach, its definition, and scope, and the debates around it, as well as the main characteristics and dimensions of the concept. Additionally, the paper notes the efforts of the international community to strengthen and operationalize human security to empower individuals by creating and giving access to new opportunities, which would then potentially lead to their country’s sustainable development. It also informs on the diversity of challenges to human security in today’s world which retard the economic growth in separate suffering states or regions and even the whole world, impedes on the human development goals, and thus dampens prospects for the country’s prosperity.